Comparative analysis of INTERGROWTH-21st and Fenton growth charts for birthweight classification in a multiethnic Asian cohort: a cross-sectional study - Suresh Chandran; Fabian Yap; Daniel Chan; Ruther Teo Zheng; Eirena Beh; Thurston Yan Jia Heng (BMJ Paediatrics Open)
Objective The objective of this study is to evaluate the impact of using International Fetal and Newborn Growth Consortium for the 21st Century (INTERGROWTH-21st) (IG-21) growth standards compared with Fenton growth charts on birthweight classification in a multiethnic newborn cohort in Singapore.Design Cross-sectional study.Setting KK Women’s and Children’s Hospital, Singapore.Patients Study population included 2541 babies born between 16 December 2019 and 16 March 2020.Interventions None.Main outcome measures Birthweight classifications of small for gestational age (SGA), appropriate for gestational age (AGA) and large for gestational age (LGA) were assessed using IG-21 and Fenton growth charts. The level of agreement between the two charts was measured using Cohen’s kappa coefficient (K).Results Of 2541 neonates, 171 (6.7%) had discordant birthweight classifications. The kappa coefficient indicated moderate overall agreement (K=0.79) between the charts, with decreasing agreement from preterm (K=0.88) to full-term categories (K=0.71). The largest discordance was observed in 98 (60.5%) neonates classified as LGA by IG-21 but AGA by Fenton. In comparison, 60 (2.9%) neonates classified as AGA by IG-21 were SGA by Fenton, while 13 (4.6%) were SGA by IG-21 but AGA by Fenton.Conclusions The study found discrepancies in birthweight classification between IG-21 and Fenton growth charts, with Fenton charts overclassifying SGA and underclassifying LGA in our study population. These findings suggest the potential need to integrate IG-21 growth standards into local practice to improve accuracy in neonatal growth assessment. Further research is necessary to evaluate the clinical implications of these discordant classifications on neonatal outcomes.